Adverse effects of pneumonia on physical functioning in nursing home residents: Results from the INCUR study. (July 2016) - Hoogendijk, Emiel O.; Del Campo, Natalia; Rolland, Yves; Demougeot, Laurent; Gérard, Stéphane; Vellas, Bruno; Cesari, Matteo
Highlights: This study investigated the impact of nursing home-acquired pneumonia on levels of physical functioning. Pneumonia events have adverse effects on physical functioning, and mainly affect independence in mobility. This study shows the importance of adequately preventing and managing pneumonia in the nursing home. Abstract: Background: Pneumonia is a very common infection in the nursing home, but little is known about its effects on levels of individual functioning. The aim of this study was to examine adverse effects of pneumonia events on physical functioning in nursing home residents. Methods: Data were used from the INCUR study, a 1-year prospective cohort study of older residents from 13 nursing homes in France. The sample consisted of 716 residents, who were assessed at baseline, 6 and 12 months. Pneumonia diagnosis was based on clinical conditions documented in medical records. Physical functioning was measured by Activities of Daily Living (ADL). Longitudinal associations between pneumonia and physical functioning were explored using Generalized Estimating Equations (GEE). Results: Of 716 participants, 145 (20%) had one or more pneumonia events during 12 months follow-up. Mean age of the participants was 86.0 (SD = 7.4) years, and 76% of them were female. Overall, participants had relatively low levels of physical functioning at baseline (Mean ADL = 2.4 out of 6, SD = 1.8). The GEE analyses adjusted for age, gender, baseline physical functioning, and hospitalization during follow-up showed that pneumonia events had adverse effects on ADL functioning (B = −0.21, SE = 0.08, p = 0.008). Pneumonia events were mainly associated with loss of independence in transferring from bed to chair and bathing. Conclusions: In a population of nursing home residents where levels of physical functioning were already relatively low, pneumonia events were associated with loss of physical functioning. These results highlight the importance of preventive interventions aimed at reducing pneumonia in nursing home residents.